Collaborative Design Practices in Technology Mediated Learning - Seitamaa-Hakkarainen, Pirita; Hakkarainen, Kai (Design and Technology Education: An International Journal, 2012)
The present article examines how practices of computersupported collaborative designing may be implemented in an elementary classroom. We present a case study in which 12-year-old students engaged in architectural design under the guidance of their teacher and a professional designer. The students were engaged in all aspects of design processes, such as analysing the design of existing houses, analysing the building site, determining building volume, design facades, and floor plans; they formed seven teams, each of which had its own house to design. The data-analysis relied on the Knowledge Forum database, consisting of students’ notes, pictures, sketches, and photos. The participants’ quantitative contributions to the database were analyzed with Analytic ToolKit which underlies Knowledge Forum. A qualitative content analysis was performed to the KF notes produced by the student teams; a theory and data-driven approach for categorizing the content of the notes was employed. The results revealed that the student teams considered various design constraints and familiarized themselves with their own building site and regulations regarding their permitted building volume. They constructed environmental models and scale models, and made the calculations of gross floor volume; scale drawings were inserted to KF’s Environmental Model view as pictures and texts. The results indicated that parallel working with conceptual (design ideas) and material artefacts (architectural models, prototypes of apartments, figures) supported one another. The intent was that involving students in modeling practices would help them build domain expertise, epistemological understanding, and skills to create and evaluate knowledge. Further, implications for designing technology-mediated collaborative design processes are discussed.